Doing communication science: thoughts on making more valid claims. Issue 3 (2nd July 2020) - Kelly, Stephanie; Westerman, David
ABSTRACT: As part of this special issue on validity, this essay addresses practices for research in both measurement and methodology through the lens of the philosophy of science. The essay has three primary objectives. First, it seeks to outline seminal characteristics of science, identifying practices that scientists must adopt in research for their work to be more scienctific . Second, the essay notes best practices for conducting science in the field of communication. Finally, the article concludes with discussion of the future of communication science.